Kertas Berpetak pada Pembelajaran Perbandingan Senilai - Rahmawati, Rahmawati; Somakim, Somakim; Susanti, Ely (Jurnal Elemen, 2016)
This study aims to generate trajectories of students in learning by using a comparison worth growing terraced paper of form informal toward formal shape. The method used in this research is the research design consisted of three stages, namely the preliminary, design experiments and retrospective analysis. In this study, a series of learning is designed and developed based on the notion of the learning process and approach PMRI. This research was conducted in SMP PGRI 1 Palembang by involving students in grade VII.2 totaling 30 students. This research produces Learning trajectory (LT), which includes three activities namely 1, activity starts from drawing two wake up the same but different size, measure each side at the wake and determine the corresponding sides to determine the ratio. Activity 2, the activity determines the relations between the two ratios to determine whether the two ratios is a comparison worth or not. Activity 3, resolve issues relating to the comparative worth of daily life-today. Results of the experiments showed that a series of learning activities that have been done to help improve students understanding of learning valued comparison.